Additive manufacturing of poly[(R)‐3‐hydroxybutyrate‐co‐(R)‐3‐hydroxyhexanoate] scaffolds for engineered bone development. (30th May 2014) - Mota, Carlos; Wang, Shen‐Yu; Puppi, Dario; Gazzarri, Matteo; Migone, Chiara; Chiellini, Federica; Chen, Guo‐Qiang; Chiellini, Emo
Abstract: A wide range of poly(hydroxyalkanoate)s (PHAs), a class of biodegradable polyesters produced by various bacteria grown under unbalanced conditions, have been proposed for the fabrication of tissue‐engineering scaffolds. In this study, the manufacture of poly[( R )‐3‐hydroxybutyrate‐ co ‐( R )‐3‐hydroxyhexanoate] (or PHBHHx) scaffolds, by means of an additive manufacturing technique based on a computer‐controlled wet‐spinning system, was investigated. By optimizing the processing parameters, three‐dimensional scaffolds with different internal architectures were fabricated, based on a layer‐by‐layer approach. The resulting scaffolds were characterized by scanning electron microscopy, which showed good control over the fibre alignment and a fully interconnected porous network, with porosity in the range 79–88%, fibre diameter 47–76 µm and pore size 123–789 µm. Moreover, the resulting fibres presented an internal porosity connected to the external fibre surface as a consequence of the phase‐inversion process governing the solidification of the polymer solution. Scaffold compressive modulus and yield stress and strain could be varied in a certain range by changing the architectural parameters. Cell‐culture experiments employing the MC3T3‐E1 murine pre‐osteoblast cell line showed good cell proliferation after 21 days of culture. The PHBHHx scaffolds demonstrated promising results in terms of cell differentiation towards an osteoblast phenotype. Copyright © 2014 John Wiley & Sons, Ltd.